Επιχειρηματικότητα, δημιουργικές βιομηχανίες και νέα επιχειρηματικότητα - Βαλιαντή, Φωτούλλα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ). Εργαστήριο Βιομηχανικής και Ενεργειακής Οικονομίας, 2015)
The aim of this diploma thesis is to analyse entrepreneurship that deals within the so-called creative industries (creative sectors) and the relevant comparison with entrepreneurship from other sectors . At the first section of the diploma thesis the relevant definitions of the creative industries are presented, while the Global Entrepreneurship Monitor (GEM), that is used in the analysis is described. In particular, for this diploma we use data from annual surveys conducted in European countries from 2005 to 2008. SPSS 20 was used for the data analysis. The main indicators of entrepreneurship in GEM both of early-stage entrepreneurs, as well as the established entrepreneurs were analysed. The main conclusions of the study show that early stage entrepreneurs who are involved in creative industries differ from the others in the following features: Male gender is superior to that in non-creative industries. Early stage entrepreneurs in creative industries seem to be younger aged between 25-34 years, whereas they seem to expect some good opportunities for starting a business in the next six months, to a greater extent. Their motive for exploiting a business opportunity was the greatest independence, however, necessity entrepreneurship is sufficiently reduced in creative industries , Finally, creative venture seem to be more exportive, whereas the technological level is higher in creative industries, than in non creative industries.